Antioxidant and anti-inflammatory activities of brown marine alga, padina minor yamada - Peerapornpisal Y. (2014)
Padina minor Yamada is a brown marine alga found in abundance at the coastal area of the Gulf of Thailand and the Andaman Sea. The aqueous extract of P. minor (Aq. P) showed antioxidant activity when tested in superoxide and hydroxyl radical scavenging, metal chelating and reducing capacity assays. Although the concentrations of Aq P. for antioxidant activity were much higher than that of standard drugs when tested in various assays, their maximal effects were approximately the same. Topical application of Aq. P on the rat ear could lessen the ear edema induced by ethyl phenylpropiolate (EPP), suggesting it possesses an anti-inflammatory activity. Interestingly, safety of the Aq. P to be used as a nutraceutical and a cosmeceutical were demonstrated according to the acute toxicity tests in rats and the irritation tests in rabbits, respectively. No signs of acute toxicity and skin irritation were observed. The findings therefore provide the evidence to substantiate the nutraceutical and cosmeceutical potential of P. minor.